Development of Soundness Assessment Procedure for Concrete Members Affected by Neutron and Gamma-Ray Irradiation - Maruyama, Ippei; Kontani, Osamu; Takizawa, Masayuki; Sawada, Shohei; Ishikawao, Shunsuke; Yasukouchi, Junichi; Sato, Osamu; Etoh, Junji; Igari, Takafumi (Journal of Advanced Concrete Technology, 2017)
In 2008, Nuclear and Industrial Safety Agency (NISA) (currently integrated to the Nuclear Regulatory Authority) launched a project to develop a soundness assessment method for concrete members subject to a radiation environment. Presently, the soundness of concrete members subject to radiation is evaluated based on whether the predicted fast neutron fluence and gamma-ray dose values are lower than specific reference values in Japan, which are 1×1020 n/cm2 and 2×105 kGy, respectively. These reference values were determined based on report by Hilsdorf et al. This project begins by reviewing Hilsdorf et al.’s report, and we find that the scientific evidence for the current reference values is weak. We thus conclude that new experimental research is required to assess the current reference values and to propose a new alternative soundness assessment procedure if needed. We quantitatively evaluated the influence of neutrons, gamma-rays, and the resultant heating and drying processes on the strength of concrete as well as their underlying mechanisms. The irradiation experiments confirmed the degradation mechanism of concrete due to neutron irradiation. The main reason for this degradation is the metamictization of rock-forming minerals, which, in turn, leads to aggregate expansion. Due to aggregate expansion, cracks around aggregates form, which reduce the compressive strength and Young’s modulus of concrete. Among the rock-forming minerals, α-quartz is the most sensitive to neutron radiation. 60Co gamma-ray irradiation experiments demonstrated that concrete strength increased as the gamma-ray dose and gamma-ray flux does not have a dose-rate impact on the first radiolysis of evaporable water in cement paste within the present study. The effect of gamma-ray irradiation on the properties of concrete is equivalent to that of heating and drying. Concrete strength alteration due to heating and drying is attributed to the colloidal and porous nature of hardened cement paste and crack formation around the aggregate due to a mismatch in the volume changes of the mortar and aggregate. In addition, a numerical analysis code called DEVICE (Damage EValuation for Irradiated ConcretE) is developed to harness knowledge obtained from concrete samples to predict the distribution of the physical properties in concrete members and their changes over time. From these fundamental studies, we propose a new soundness assessment procedure for concrete members subject to radiation. We also recommend a new radiation-induced strength-degradation reference value of 1×1019 n/cm2 for fast neutron.